Loop Biceps Tenotomy: An Arthroscopic Technique for Long Head of Biceps Tenotomy - Goubier, Jean-Noel (Elsevier, 2014)
The long head of the biceps tendon is frequently involved in shoulder pathologies, often in relation to inflammatory or degenerative damage to the rotator cuff. Biceps tenodesis in the bicipital groove and tenotomy are the main treatment options. Tenotomy of the long head of the biceps tendon is a simpler and quicker procedure than tenodesis, and it does not require the use of implants. However, retraction of the biceps tendon, leading to Popeye deformity, and biceps muscle cramps are common complications after tenotomy. Therefore we propose an arthroscopic technique for tenotomy that limits the risk of Popeye deformity. This procedure consists of creating a loop at the severed end of the biceps tendon, which prevents the tendon from retracting into the bicipital groove.